Hubungan Frekuensi Menyikat Gigi dengan Tingkat Kebersihan Gigi dan Mulut Siswa Sekolah Dasar - Arfiah Jauharuddin; Fidzah Nurfajrina Murad; Dwi Rezky Aulyah; Faradillah Usman; Suciyati Sundu (Universitas Muhamadiyah Manado, 2023)
Brushing teeth properly and correctly is an important factor for maintaining oral health. The success of maintaining oral and dental health is also influenced by the pattern of brushing teeth. The pattern of brushing teeth includes the technique of brushing teeth, the time and frequency of brushing teeth. The problem in this study is poor oral and dental hygiene in elementary school children (46.4%). Dental and oral hygiene is an important factor for dental and oral health to be free from disease, therefore dental and oral hygiene must be maintained and maintained in order to create optimal health. Objective: Knowing the relationship of brushing patterns with dental and oral hygiene in elementary school children. Method:. Collecting data on brushing patterns by filling out a checklist on the observation sheet and interview sheet. Collecting dental and oral hygiene data using an examination sheet. Respondents in this study amounted to 110 students, who were taken by simple random sampling. The data analysis technique used was the Chi-square test. Results: The pattern of brushing teeth in the poor category is 89 respondents (80.9%), dental and oral hygiene is in the bad category, namely 51 respondents (46.4%). The results of the Chi-square test are P value 0.002.Conclusion: That there is a relationship between the pattern of brushing teeth with dental and oral hygiene in elementary school children.